Diagnóstico del sector productivo camaronero en agua dulce del cantón Chone - Hidalgo Cedeño, Ángel Josué (2020)
The current investigation had the purpose of carrying out a diagnosis of the freshwater shrimp production sector in Chone canton, with the aim of establishing a baseline of its current situation. The applied methodology consisted of three phases: in the first phase, the active shrimp farms were characterized, through an interview with the president of the association and the preparation of an observation sheet that allowed increasing the study sample, in order to determine the organizational structure of the shrimp farms; in the second phase the economic, social and financial situation of the sector was determined by applying a survey to producers and subsequently analyzing the elements of cost and examining production using a Gantt chart, and in the third phase, an action plan was proposed and socialized to the producers and representatives of the association, consisting of activities that contribute to counteracting the problems identified and strengthening productivity. Finally, it was concluded that this aquaculture sector in Chone canton, is composed of associated and non-associated shrimp farms, both with an informal organizational status, is an important source of employment and economic development, integrates actions of social and environmental responsibility in its production processes, presents difficulty in obtaining profits, due to the lack of a costing system and the overvaluation of the items that make up the cost elements, as well as the lack of planning documents that allow to provide scenarios and establish coping strategies.